Hubungan Presepsi Dukungan Sosial Teman Sebaya Dan Supervisor Dengan Tingkat Burnout Mahasiswa Saat Melaksanakan Praktikum : Studi Pada Mahasiswa Ilmu - Paradasa, Zatadini K; Hati, Getar (Jurnal Ilmu Kesejahteraan Sosial, 2024)
Students assigned with field practice (practicum) are prone to experiencing burnout. This study focuses on Social Welfare students who are currently undertaking practicum assignments. Burnout conditions can disrupt their social functioning and impacting target groups, institutions, and universities. One factor related to burnout is social support perceived by students. However, there is still minimal research related to burnout and social support among practicum students from social departments in Indonesia. Therefore, this study aims to describe the relationship between social support and burnout. This study uses a quantitative approach with descriptive objectives. The sample in this study was all UI Social Welfare practicum students in the even semester of 2023/2024, with a final sample of 75 students. Data collection was carried out by distributing questionnaires in June 2024. The data analyzed univariately and bivariately using Kendall's tau-b test with SPSS. Univariate analysis showed that 70.7% of students experienced moderate levels of burnout, 73.7% of students had moderate perceptions of peer social support, and 65.3% of students had moderate perceptions of social support from school supervisors. Kendall's tau-b test results indicated a significant but weak negative relationship between peer social support and burnout (T = -.334, p < 0.05) and between school supervisor social support and burnout (T = -.322, p < 0.05).